Caracterizações de filmes finos de titanato de cobalto para aplicação em sistemas memristivos - Góis, Meirielle Marques de (2020)
We investigated thin films of P t/Co0,2T iO3,2/IT O and P t/Co2T i0,7O4−δ/IT O with different thicknesses using the magnetron sputtering technique, in order to evaluate its application potentials in memristors devices. We used characterizations by X–ray diffraction (XRD), X–ray reflectometry (XRR), Rutherford backscattering spectrometry (RBS), X–ray photoelectron spectroscopy (XPS), UV–VIS spectroscopy, electrical and magnetic analyzes. The systems with low crystallinity structure presented multifunctional performance revealing binary and analog resistive switching properties. The presence of oxygen vacancies confirmed by XPS and UV–VIS absorption are active agents in the electrical transport process of filamentary switching and adaptive conductance activity. Retention tests at high (HRS) and low (LRS) resistance regimes revealed a good ratio between resistive states, with magnitudes in the order of 104 and 106 . In addition, the existence of Co2+ and Co3+ ions provided a paramagnetic behavior at 300 K and weak ferrimagnetism at 5 K, as well as a magnetic effect capable of influencing the electrical response of the devices.